Bifacial Vertical Photovoltaic System Design for Farming Irrigation System - Ghalia Nasserddine; Mohammad Nassereddine (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
The increase in population leads to an upsurge in food demands which also expend the agriculture activities. A wide range of electrically powered machines is essential for the success of modern agriculture setup.  Farming required electrical power for numerous activities such as irrigations and electric tractors. A large number of farms are located in remote areas where access to electricity could be costly. Also, farms that are located within the electrical grid suffer from the cost of electricity bills. In line with the United Nations' recommendations to deploy renewable energy sources for electrical power generations, photovoltaic systems are installed for farming activities across countries. A photovoltaic system converts solar radiation into electrical power and with the use of advanced power electronics devices, PV technologies become very attractive to farmers. The work in this paper capture the PV system operation for farming purposes. The contents cover standard PV panels and their current deployment layout for farms. The paper introduces the bifacial panel's concept and its novel layout. Furthermore, the paper proposed a novel installation layout for bifacial panels to support the farm electrical demands. The case study, which is based on three-phase irrigation pumps, explains and verifies the advanced role that the proposed layout of bifacial panels over the standard one. The advantages of the proposed installation layout are also included